The Ethical Standards Prescribed in The Qur'an - Zamakhsyari bin Hasballah Thaib (Rabbanica: Journal of Revealed Knowledge)
This research is to understand the ethical tenets elucidated in the Quran and their impact on the formation of a virtuous society, starting with the nurturing of individuals who possess high moral standards. Morality is essential for the development, maintenance, and improvement of any community, as well as strengthening the connections between individuals within it. This study aims to clarify the moral principles delineated in the Qur'an by investigating its origin and characteristics. Additionally, it seeks to understand the moral standards that encompass both an individual's internal convictions and beliefs as well as their external conduct and demeanor. The method entails scrutinizing the ethical doctrines present in the Quran's verses. This study employs a thematic interpretation methodology that incorporates a deduction-based analytical descriptive technique. The study's main conclusions, "Morality in the Perspective of the Qur'an," focus on the essential steps and measures required to foster virtue and achieve happiness as a morally upright person. The Qur'an portrays morality as a practical necessity that demands immediate action rather than simply theoretical contemplation. The Qur'an asserts that the right moral principles are derived from divine revelation rather than from rationality or cultural conventions. The moral convictions that govern the sentiments of a Muslim revolve around fundamental principles such as tawhid (the unity of God), tawakkal (dependence on God), intention, and love.